Fenômenos ondulatórios e os instrumentos musicais: ensino por meio dos três momentos pedagógicos - Oliveira, André Luiz (2018)
The objective of this work was to evaluate if a didactic sequence for the teaching of wave phenomena, using musical instruments, stimulates the autonomy, the critical thinking, the creativity, the capacity of abstraction and the epistemological curiosity of the students. The Three Pedagogical Moments (Três Momentos Pedagógicos) of Delizoicov and Angotti were used as teaching technique. This qualitative research was carried out with students of the second year of high school, in a public school of the city of Goiânia. For the data collection, the classes were recorded in audio and vídeo and transcribed and analyzed. In the development of the Three Pedagogical Moments, students were able to demonstrate if they achieved the qualifications of the objective. During the problematization (first moment) and the organization of the knowledge (second moment), the students were able to identify phenomena of their daily life that involved the wave phenomena, exposing their doubts the personal observations. Six classes were used to carry out the research, and the students' speeches and discussions were analyzed. In these analyzes, according to the view of Paulo Freire, it was observed several moments in which the students demonstrated critical thinking, abstraction capacity and epistemological curiosity, indicating that the dynamics was able to promote an education in the critical perspective, thus avoiding a scientific literacy of the banking type.